Recent progress on transforming crude glycerol into high value chemicals: a critical review. Issue 3 (4th May 2019) - Sivasankaran, Chozhavendhan; Ramanujam, Praveen Kumar; Balasubramanian, Bharathiraja; Mani, Jayakumar
ABSTRACT: Glycerol has been known from ancient times. The microbial synthesis of glycerol has declined due to difficulty in separation and purification from broth and it is unable to compete with chemical synthesis from petrochemical feedstock. The rapid expansion of biodiesel industries generates a tremendous quantity of waste glycerol as the main by-product; thus, the disposal of it becomes an environment threat. Purification of crude glycerol for industrial usage is expensive because of the flooded impurities present in it. The high degree reduction of carbon in crude glycerol confers the production of value added products through fermentation process. The use of renewable waste substrate reduces the waste treatment cost and increases the economic value of bio-based industries. This review condenses the impact of impurities in crude glycerol and its challenge on the microorganism for bioconversions and the need for partial purification.